PENGARUH PEMBERIAN JUS BUAH NANAS TERHADAP PENYEMBUHAN LUKA PERINEUM DERAJAT 2 PADA IBU POST PARTUM - Insani, Septa Dwi; Pratama, Nanda (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Perineal tears are those that happen there. when the baby is born spontaneously or episiotomy. If the perineal tear is not treated immediately, infection will occur and delay wound healing. Infection ranks as the fourth highest cause of the Maternal Mortality Rate (MMR). Efforts are being made to prevent infection and accelerate wound healing with alternative medicine by giving pineapple which is processed into pineapple juice. Pineapple contains the enzyme beromelain where this enzyme aims to heal all wounds, both perineal wounds. This study aims to determine the effect of giving pineapple juice on the healing of 2nd degree women with postpartum perineal wounds at the Tanjung Pratama Clinic, Deli Tua District, Deli Serdang Regency. This study used a quasi-experimental study type with a group design pretest posttest. The population in this study was postpartum women who experiencand ed perineal tears Using the technique of purposive sampling, around 16 people were sampled. Data analysis using the Wilcoxon test. Prior analysis results being given the average value of perineal wound healing was 6.13 (50%) while the average perineal wound healing after being given an average value of 0.38 (81.3%) obtained a p value = 0.000 0.05. this means that giving pineapple juice has a healing effect on perineal wounds.